Tail risk connectedness during geopolitical shocks: assessing the impact of Russian-Ukraine conflict on G7 stock markets - Hu, Y.; Corbet, S.; Hou, Y.; Lang, C.; Oxley, Leslie (Taylor & Francis Group, 2024)
This study investigates the impact of the Russian-Ukraine war on the tail risk connectedness among G7 stock markets using a TVP-VAR frequency connectedness approach and several robustness testing procedures. Such work focuses on the dynamics of tail risk connectedness during and after the conflict. Results identify that the conflict significantly increased tail risk connectedness among G7 stock markets, with the highest estimated levels observed two- and three months thereafter during the implementation of international targeted sanctions packages, signalling the strong persistence of short-term and total connectedness, respectively. The increase in connectedness can be attributed to factors such as heightened geopolitical and economic uncertainty, increased interconnectivity due to elevated risk and concomitant safe-haven behaviour, financial contagion, disrupted supply chains, and shifts in investor sentiment. Results emphasize the importance of monitoring and managing tail risk connectedness among financial markets, providing valuable insights for macroprudential policy design and promoting financial stability in the face of geopolitical risks.